OC-060 A clinically applicable three gene signature is independently highly prognostic in oesophageal and junctional adenocarcinoma. (23rd September 2015) - Peters, C J; Rees, J R E; Hardwick, J S; Vowler, S L; Ong, C J; Zhang, C; Save, V; O'Donovan, M; Rassl, D; Caldas, C; Alderson, D; Hardwick, R H; et al.
Abstract : Introduction: The incidence of oesophageal and junctional adenocarcinoma has increased sixfold in the last 30 years and 5-year survival remains <14%. Most patients present with advanced disease and current staging is limited in its ability to predict survival. We aimed to generate and externally validate a molecular prognostic signature for oesophageal adenocarcinoma. Methods: Gene expression profiling was performed and the resulting 42 000 gene signatures correlated with clinical features for 91 snap frozen oesophageal and junctional resection specimens. External validation of selected targets was carried out on 371 independent cases using immunohistochemistry to maximise clinical applicability. Results: Gene expression profiles were obtained from 75/91 of the samples (82%). 119 genes were significantly associated with survival and 270 genes with the number of involved lymph nodes. Ten of these genes were taken forward to external validation at the protein level. Three genes were prognostic in the external validation data set (TRIM44, SIRT2 and PAPSS2). Patients with dysregulation of none of these three genes had a significantly better outcome (5-year survival 48%) than those with dysregulation of one gene (5-year survival 29%), who in turn did better than those with two or more genes dysregulated (5-year survival 15%) (p=0.004). The three gene signature was independently prognostic in a multivariable model together with the existing clinical TNM staging system (p=0.003). Conclusion: We have generated and externally validated an immunohistochemical prognostic gene signature which is independently highly prognostic in an external validation data set. In addition these three genes are possible therapeutic targets raising the possibility of personalised therapy based on a patient's molecular prognostic signature. Our three gene signature is suitable for application in routine clinical practice and this study may provide a framework for similar future projects.